The figure is below.
To be in equilibrium the sum of all three forces (considered as vectors) from the springs need to be zero.
F1+ F2+ F3= 0
On the vertical axis one has
`F1_v =F2_v (= kx*sin(60))` It results `F3_v =0 N`
On the horizontal axis
`F3_h =F1_h +F2_h = kx*cos(60) +kx*cos(60) =2kx*cos(60)`
If `l` is the extension of spring S3 the above equality is
`l =2x*cos(60) =2x*1/2 =x`
For equilibrium the extensions of all three springs (making with each other an angle of 120 degree) are the same (`= x)`